A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from China - Gildenkov, Mikhail Yu. (Zootaxa, 2022)
A new species of the subgenus Troginus Mulsant et Rey 1878 from China is described and illustrated: Carpelimus (Troginus) taipoensis Gildenkov sp. n.